The Effectiveness Tera Aerobic And Nutrition Management Towards The Heart Fitness Of Prospective Haji Conventions - et. al., Rini Fahriani Zees, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Physical fitness or cardiovascular fitness (VO2Max) is a determining factor for the health status of the pilgrims. Cardiovascular fitness can be improved in several ways, including exercise and nutrition management.This study aims to determine the effectiveness of exercise and nutritional management on the heart and lung fitness of the pilgrims. Quasi-experimentalmethodusing pretest-posttest non-equivalent control group design and using the t-test on 34 prospective pilgrims showed. This study usedtheRockpot Instrument.Result:Therewas a significant effect between exercise and nutritional management on cardiovascular fitness. (P-Value: 0.05 and 0.00,α: 0.05).Conclution:The variablethat has themostinfluenceoncardiovascularfitnessisexercisemodifiedwithnutritionalmanagement. Gymnastics exercises and counseling on nutrition using video lessons are very effective in improving heart-lung fitness for aspiring pilgrims.